Design and Implementation of a Network Centric Appliance Platform - Pasetto, Davide; Franke, Hubertus; Schleupen, Kai; Maze, David; Penner, Hartmut; Achilles, Heather; Crawford, Catherine; Purcell, Mark (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2012)
Increasing demands on end-to-end solution performance has lead to a generation of workload optimized systems and appliances, with tightly integrated hardware and software delivering substantial improvements over general purpose architectures. Among the many challenges encountered in designing an appliance, the most complex one is making hardware and software high performance and, at the same time, render the system versatile enough to support as many workloads as possible. This paper provides a high level overview of the design and implementation process of such an appliance architecture, as realized by the IBM PowerEN team. The platform includes new silicon (the PowerEN processor), a novel system level board (Chroma card), system software and development kit, as well as end user applications for different industry domains. The solution has been completely designed by the team, starting from concept, to architecture, to implementation and delivery. The paper describes the most important characteristics of the platform, detailing how these influence its capability of supporting multiple optimized workloads.